Repositionable self-expanding aortic bioprosthesis - Gomes Botelho Quintas, Bruna; Katus, Hugo; Bekeredjian, Raffi (Expert review of medical devices, 2017)
Introduction: Transcatheter aortic valve implantation/replacement (TAVI or TAVR) has been established as a first line therapy in patients with symptomatic severe aortic stenosis (AS) at high or prohibitive surgical risk and as an alternative in elderly patients with intermediate surgical risk. Since its first-in-human procedure in 2002, the past 15-years have shown rapid developments in TAVI technology with the introduction and further improvement of new transcatheter heart valves (THV).Areas covered: There are currently several THV systems available, based on balloon-expandable, self-expandable or other technologies. Some of these are repositionable and retrievable even after partial or full deployment, potentially reducing the risk of malpositioning. The aim of this review is to describe such repositionable self-expandable THV systems.Expert commentary: Repositionability potentially represents a crucial step towards higher safety and efficacy of TAVI. It is unclear if full self-expandability or a combination of self and mechanical expansion will be more advantageous.